2015
DOI: 10.3892/or.2015.3944
|View full text |Cite
|
Sign up to set email alerts
|

p62 participates in the inhibition of NF-κB signaling and apoptosis induced by sulfasalazine in human glioma U251 cells

Abstract: Nuclear factor-κB (NF-κB) is constitutively activated in most malignant gliomas and is involved in cancer progression and drug resistance to chemotherapy. Sulfasalazine (SAS) is a classic inhibitor of NF-κB. Apoptosis and autophagy were induced by SAS accompanied by inhibition of NF-κB signaling in U251 cells. Inhibition of autophagy by 3-MA suppressed the effects of SAS on NF-κB signaling and apoptosis in U251 cells. Multifunctional scaffold protein p62 is well known as an autophagy marker protein and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The P62 knockdown coordinates a series of antiproliferative responses and may facilitate dedifferentiation of mature hepatocytes into nestin-positive progenitor-like cells. 23 , 24 Herein, our results showed that P62 cooperates with TNF-α to promote the malignant transformation of mesenchymal stem cells. The involvement of promotion of the malignant transformation of mesenchymal stem cells is supported by results from two parallel sets of experiments: (1) P62 triggers mesenchymal stem cells’ malignant transformation in injury inflammatory mouse liver and (2) excessive P62 cooperates with TNF-α to accelerate mesenchymal stem cells’ malignant growth in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 64%
“…The P62 knockdown coordinates a series of antiproliferative responses and may facilitate dedifferentiation of mature hepatocytes into nestin-positive progenitor-like cells. 23 , 24 Herein, our results showed that P62 cooperates with TNF-α to promote the malignant transformation of mesenchymal stem cells. The involvement of promotion of the malignant transformation of mesenchymal stem cells is supported by results from two parallel sets of experiments: (1) P62 triggers mesenchymal stem cells’ malignant transformation in injury inflammatory mouse liver and (2) excessive P62 cooperates with TNF-α to accelerate mesenchymal stem cells’ malignant growth in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 64%
“…P62 is a scaffold protein involved in a variety of cellular processes including NF-kB-signaling [ 31 , 50 , 51 ]. Recently, a correlation of p62 expression with clinicopathologic parameters has been shown for prostate cancer and gastrointestinal carcinoma [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, p62 knockdown reduced both the proliferation of cancer cells and tumor growth. Although the regulation of mitochondrial integrity by mitophagy seems to be the principal mechanism by which p62 promotes cancer cell survival, it remains to be clarified the impact of p62 in the regulation of important signaling pathway in cancer, such as NF-κΒ 60,77,[79][80][81] . p62 alters IKK/NF-κΒ signaling by promoting IκΒα phosphorylation and its autophagy-dependent degradation 20,82,83 .…”
Section: Nf-κb Regulates Autophagy In Cancer Cellsmentioning
confidence: 99%